2021
DOI: 10.3390/ijms22189664
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticle Technology for Delivering Biologically Active Fatty Acids and Monoglycerides

Abstract: There is enormous interest in utilizing biologically active fatty acids and monoglycerides to treat phospholipid membrane-related medical diseases, especially with the global health importance of membrane-enveloped viruses and bacteria. However, it is difficult to practically deliver lipophilic fatty acids and monoglycerides for therapeutic applications, which has led to the emergence of lipid nanoparticle platforms that support molecular encapsulation and functional presentation. Herein, we introduce various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 155 publications
(183 reference statements)
0
18
0
Order By: Relevance
“…Such membrane interactions can be observed in LDH release studies and were reported to be considered beneficial for particle uptake when they do not affect cell viability. ( Tan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such membrane interactions can be observed in LDH release studies and were reported to be considered beneficial for particle uptake when they do not affect cell viability. ( Tan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that shorter-chain antimicrobial lipids typically have greater solubility in aqueous environments as well, these findings support that undecanoic acid and monoundecanoin are attractive candidates for further development as membrane-disrupting antimicrobial lipids. Note that undecanoic acid is already used within antifungal creams while our results suggest that it might also be useful for other aqueous-based formulations such as lipid-based nanoparticles [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, several other lipid-based NPs, such as nanostructured lipid carriers (NLCs), lipid nanocapsules (LNCs), polymer lipid NPs, and lipid-based micelles, were developed to deliver various drugs. For instance, Kiss et al developed DEX-encapsulated nanostructured lipid carriers for ophthalmic use . Toxicity assessments on human cornea cells showed favorable ophthalmic tolerability of NLCs .…”
Section: Dexamethasone Delivery Systemsmentioning
confidence: 99%